Giaccardi Inequality for Modified h-Convex Functions and Mean Value Theorems - Yonghong Liu; Wasim Iqbal; Atiq Ur Rehman; Ghulam Farid; Kamsing Nonlaopon (Journal of Function Spaces)
In this article, we consider the class of modified h−convex functions and derive the famous Giaccardi and Petrovic′ type inequalities for this class of functions. The mean value theorems for the functionals due to Giaccardi and Petrovic′ type inequalities are formulated. Some special cases are discussed by taking different examples of function h.